Russian-Turkish relations after 1991 and their future prospects (قضايا سياسية, 2025)
The breadth of the Russian-Turkish relations extending over five centuries has formed a rich history that includes among its folds all forms of international relations between wars، conflict،cooperation، competition، harmony and rupture،and the geographical proximity that actually ended after the Second World War had a reason for many of those events until the twenty-first century came. So that the first decade of it witnessed a mixture of tension، mistrust and cooperation in various fields، so that at the beginning of the second decade of it، the relationship of the two parties entered the stage of the conflict، which reached its climax with the exacerbation of the Syrian crisis and the intersection of the interests of the two countries with itAmong those contradictions between the two countries، but they were keen on continuing the economic relations between them to prove that economic cooperation is present in moisturizing the atmosphere at all times، and that is why the research contains many contradictions in the relationship between the two countries،wherever the reader finds these contradictions،he will know that this is due to the nature of The relationship and its impact on regional and international changes.